FACTORS RELATED TO THERAPEUTIC COMMUNICATION ABILITY IN THE PROFESSIONAL STUDENTS OF INDONESIAN MEDICAL NERS STIKES IN 2022 - Sinta, Sinta Nuriyah; Meriyandah, Hilda; Agustina, Lisna (Rena Cipta Mandiri, 2024)
Communication in a nursing setting is called therapeutic communication. Therapeutic communication is the basic foundation of all nurse interactions with clients and is the main method of implementing the nursing process. The stages of therapeutic communication include the pre-interaction phase, the orientation phase, the work phase, the termination phase. Factors influencing therapeutic communication include perception, emotion, value, level of knowledge, age, gender and cultural background. The research used is quantitative by using Descriptive Analytics with a cross sectional approach. The population in this study was 91 students of the Indonesian Ners STIKes Medistra Profession in 2022, the sample of this study was 91 students. Data collection method using non probability sampling with purposive sampling technique. Data collection is carried out with questionnaire sheets. The research analysis was carried out by means of univariate and bivariate statistical tests with the Fisher's Exact test and the Chi-Square test. Based on the results of the study, there was no sex relationship with p-value therapeutic communication ability (0.087), there was no age relationship with p-value therapeutic communication ability (0.297), no tribal relationship with p-value therapeutic communication ability (0.326). And there is a relationship of knowledge with the therapeutic communication ability of the p-value (0.000).